Camponeses Brazil's Peasant Movement in Historical Perspective (1946-2004) - Welch, Cliff [UNESP] (Sage Publications Inc, 2009)
Comparison of the histories of three leading peasant organizations in the Pontal do Paranapanema region of Brazil-the Partido Comunista do Brasil (PCB) from 1945 to 1964, the Confederacao Nacional de Trabalhadores na Agricultura (CONTAG) from 1964 to 1984, and the Movimento dos Trabalhadores Rurais Sem-Terra (MST) from 1984 to 2004-suggests that continuity is as important as change in understanding Brazilian peasant movements. The MST has been considered a "new social movement" in that it has eschewed partisan politics, incorporated families as members rather than just male heads of household, had a national scope and a participatory decision-making structure, and been attuned to the international struggle over globalization. Placing it in historical perspective makes it clear, however, that this is not the first time that militants have organized around the concept of peasants as a political identity; that while the representation of peasants in the leadership of contemporary rural labor organizations may be greater than in the past, earlier peasant leaders also struggled on behalf of their class; that earlier peasant organizations had, if not a national presence, a substantial presence in the agricultural states of the time; and that attempts at international organization to unite peasant struggles around the globe are not entirely new. This is not to deny the innovative features of contemporary movements but to suggest that the investigation of past achievements will contribute to a fuller appreciation of these movements' conditions and prospects.
Keywords: Peasants; Rural labor organizations; New social movements theory; Pontal do Paranapanema; State